Corporate Fundamentals, Bi Rate And Systematic Risk: Evidence From Indonesia Stock Exchange - Nita Puspitasari, Perdana Wahyu Santosa (Jurnal Manajemen, 2019)
The aim of this study is to understand the effect of company's fundamental factors and BI rate on systematic risk (beta) on the Indonesia Stock Exchange (IDX).Â In portfolio theory, there are two types of risk, namely systematic risk and non-systematic risk.Â The focus of this study is on systematic risk which was measured through beta (Î²), where each stock had a different beta.Â The analyses used independent variables ofÂ sales growthÂ (SG),Â net profit marginÂ (NPM),Â debt to equity ratioÂ (DER) and BIÂ rateÂ (benchmark interest rate) on stock beta.Â The data used were quarterly data ofÂ issuers listedin the LQ-45 index in theÂ period of 2009-2016 which were analysed usingÂ panel data regressionÂ method.Â The conclusion from panel data analysis ofÂ LQ-45 indexÂ is that SG, NPM and DER contribute a significant impactÂ onÂ systematic risk,Â but the macroeconomic proxy, namelyBIÂ rate, does not offerÂ significant influence on stock betaÂ (Î²).Implication: corporate fundamental factors such as sales growth, net profit margin and solvency has effect significantly on beta (Î²), however BI rate does not.